Implementasi Analisis SWOT dalam Menentukan Marketing Strategy Usaha Sablon Kaos “My Blessing Cloth” - Fadilla Anjarika Kuswisnu Wardani; Eni Setyowati (Universitas Muhammadiyah Surakarta, 2025)
T-shirt screen printing is one type of creative industry business whose development is quite rapid so that many people are in demand. My Blessing Cloth is one of the screen printing t-shirt printing businesses that has great prospects so that it can generate considerable profits in each order. The great prospect of this t-shirt screen printing business produces many competitors, this market competition can affect the sales level of My Blessing Cloth... SWOT analysis is used by business actors who aim to be able to identify a problem so that they get a new strategy that is suitable and can be applied for the progress of the business. Limited labor, lack of offline promotion and limited production facilities are weaknesses for My Blessing Cloth's t-shirt screen printing business. The amount of market competition, less strategic production locations and increasing material prices are threats to My Blessing Cloth. So that a marketing strategy can be found that can be applied by My Blessing Cloth in maintaining its business, namely, by maintaining the quality of its products in terms of materials and product durability, adding competent labor and more modern facilities so as to increase production output. In addition, product promotion by utilizing social media and e-commerce can attract consumer interest so that it has a positive impact on increasing sales of t-shirt screen printing products from My Blessing Cloth.